Entrepreneurial Intention among Postgraduate Students in Nigerian Universities: Conceptual Review - Idris, Adamu Abdullahi (American Finance & Banking Review, 2017)
Governments in most developing countries are doing their best to ensure that graduates who are not employed should engage in entrepreneurship activities which can go a long way in reducing the problem of unemployment among the youths. Nigeria is among one of those developing nations with such problem. The government has introduced some many programs and policies which are aimed at reducing poverty and will encourage self-employment among the youths. Yet, students are still lacking the intention of becoming entrepreneur. From this study, there will be need to cover the gap found in the literature and then developed a conceptual framework (from which propositions where developed. The study used factors such as entrepreneurship education, environmental factors and societal entrepreneurship attitude to explore the student’s entrepreneurial intention. These factors where adopted bases on past theoretical and empirical studies which will cover the gap and contribute to the body of knowledge in the field of literature. Finally, this study calls upon researchers and Ministry of Education to examine this propositions on how to design a more comprehensive and benefice entrepreneurship courses and curriculum to these Nigerian universities. This will aim at preparing these students to be self-employed (entrepreneurs) which will reduce and assist the government in overcoming the problem of youth poverty and unemployment in Nigeria.